Necesidades motivacionales y rendimiento académico de los estudiantes preadolescentes escolarizados en una institución educativa de Salento Quindío (2021)
The general objective of this study was to determine the relationship between motivational needs and academic performance of pre-adolescent students enrolled in an educational institution in Salento Quindío. For the fulfillment of the objective, a quantitative study with a correlational scope is structured. The sample consisted of 30 students, aged between 9 to 14 years, to whom the McClelland Questionnaire was applied to measure motivational needs. Regarding the academic performance, this was provided by the educational institution. The results indicated that the motivational needs had a moderate level in the need of achievement, and low levels in the needs of affiliation and power. A negative correlation was found in the need of achievement and academic performance; in the same way, a positive but low correlation was found in academic performance with the needs of achievement, affiliation and power. It was concluded that students are not motivated at levels that can contribute to their academic performance